2020
DOI: 10.1007/s10741-020-10024-2
|View full text |Cite
|
Sign up to set email alerts
|

Renal protection: a leading mechanism for cardiovascular benefit in patients treated with SGLT2 inhibitors

Abstract: Initially developed as glucose-lowering drugs, sodium-glucose co-transporter type 2 inhibitors (SGLT2i) have demonstrated to be effective agents for the risk reduction of cardiovascular (CV) events in patients with type 2 diabetes mellitus (T2DM). Subsequently, data has emerged showing a significant CV benefit in patients treated with SGLT2i regardless of diabetes status. Renal protection has been initially evaluated in CV randomized trials only as secondary endpoints; nonetheless, the positive results gained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 64 publications
0
27
0
6
Order By: Relevance
“…SGLT2i is able to slow the progression of CKD by reducing barotrauma and proteinuria, glomerular hyperfiltration, and intraglomerular pressure. Other studies have also shown that SGLT2i can prevent oxidative stress, hypoxia, and fibrosis of renal tubules [73]. Moreover, SGLT2i reduces the activity of the sympathetic nervous system, thereby protecting the vascular system.…”
Section: Expert Opinionmentioning
confidence: 94%
See 1 more Smart Citation
“…SGLT2i is able to slow the progression of CKD by reducing barotrauma and proteinuria, glomerular hyperfiltration, and intraglomerular pressure. Other studies have also shown that SGLT2i can prevent oxidative stress, hypoxia, and fibrosis of renal tubules [73]. Moreover, SGLT2i reduces the activity of the sympathetic nervous system, thereby protecting the vascular system.…”
Section: Expert Opinionmentioning
confidence: 94%
“…Moreover, SGLT2i reduces the activity of the sympathetic nervous system, thereby protecting the vascular system. The euglycemia, optimal blood pressure and lipid profile, and lower body weight induced by SGLT2i have been shown to protect small as well as large blood vessels [73]. Direct cardiac effects of SGLT2i have also been reported.…”
Section: Expert Opinionmentioning
confidence: 99%
“…58 The SGLT2iassociated renoprotective effects have been highlighted as a key mechanism for the reported cardiovascular benefits. 43 Meanwhile, the potential renoprotective effects of GLP-1A were attributed mainly to its impact on mitigating the progression of atherosclerosis-related vascular disease. 52 Consistently with our review findings, there are recent recommendations to consider either SGLT2i or GLP-1A as add on to metformin in patients who had mainly underlying atherosclerotic cardiovascular disease, and to consider SGLT2i first, in patients who had underlying chronic kidney disease and reduced heart failure, to be followed by GLP-1A if needed.…”
Section: Glucagon-like Peptide-1 Analogues (Glp-1a)mentioning
confidence: 99%
“…The direct mechanisms involve osmotic diuresis in overloaded cases in synergy with the given diuretic therapy and the suppression of oxidative stress and inflammation pathways. 43 Meanwhile, the indirect mechanisms include the ability to reduce blood pressure, body fat, body weight in addition to the uricosuric effect. 43 In a clinical trial, dapagliflozin was found to reduce blood pressure and body weight near the values reported for hydrochlorothiazide, although different underlying mechanisms exert diuretic effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation